Cataloging for school librarians - Kelsey, Marie Ellen 1948- (Lanham Rowman & Littlefield, 2018)
"The theory and practice of cataloging and classification for students and practitioners who need a clear sequential process to help them overcome cataloging anxiety"--Provided by publisher.
Introducing the library catalog and access to resources -- Supporting resource discovery: RDA and FRBR -- Obtaining online catalog bibliographic records -- Understanding Cataloging in Publication (CIP) -- Creating primary and secondary access points -- Creating authorized forms of names -- Creating MARC 21 records -- Cataloging books -- Cataloging non-print and electronic materials -- Cataloging serials, books in series, and graphic novels -- Using Sears list of subject headings -- Using abridged Dewey decimal classification -- Building Dewey numbers in three major areas -- Resource discovery and the Common Core state standards -- Appendix A. RDA records in MARC from OCLC.
Includes bibliographical references (pages 379-384) and index.
Keywords: Cataloging -- Handbooks, manuals, etc; School libraries -- Handbooks, manuals, etc